2014
DOI: 10.1177/1074248414536273
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological and Morphological Maturation of Murine Fetal Cardiomyocytes During Electrical Stimulation In Vitro

Abstract: The aim of this study was to investigate whether continuous electrical stimulation affects electrophysiological properties and cell morphology of fetal cardiomyocytes (FCMs) in culture. Fetal cardiomyocytes at day 14.5 post coitum were harvested from murine hearts and electrically stimulated for 6 days in culture using a custom-made stimulation chamber. Subsequently, action potentials of FCM were recorded with glass microelectrodes. Immunostainings of α-Actinin, connexin 43, and vinculin were performed. Expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 27 publications
5
21
0
Order By: Relevance
“…Aligned PCL + G scaffolds also stimulated the highest fractional release of all conditions as well as the highest spontaneous beating frequency at day 6 of culture. Cardiomyocyte organization and alignment has been shown to affect electrical function and to optimize force generation while electrical stimulation promotes cardiomyocyte elongation and alignment . Hence, the benefits of combining alignment and the presence of graphene would only be further enhanced through the addition of local electrical stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Aligned PCL + G scaffolds also stimulated the highest fractional release of all conditions as well as the highest spontaneous beating frequency at day 6 of culture. Cardiomyocyte organization and alignment has been shown to affect electrical function and to optimize force generation while electrical stimulation promotes cardiomyocyte elongation and alignment . Hence, the benefits of combining alignment and the presence of graphene would only be further enhanced through the addition of local electrical stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…As CMs undergo more coordinated and efficient electrical stimuli with the development of the mature cardiac conduction system, the CMs respond to their environment by upregulating electrophysiological structures. Studies on electrical stimuli of CMs have shown an increase in cell size, alignment, connexin-43 expression, ion channel expression, and sarcomere organization (Baumgartner et al, 2014). Overall, efficient propagation of electrical signals is a crucial aspect of CM natural developmental program and functionality.…”
Section: Natural Developmental Program That Drives In Vivo Cardiomyocmentioning
confidence: 99%
“…Not only are expression levels of these key proteins controlled via mechanotransduction pathways as discussed in the previous section, but they are also regulated via electrical stimulation. For example, cells plated on tissue culture plastic and stimulated (10 Hz, 1 V, 5 ms) for six days showed significantly greater alignment, expression of Cx43, increased ratio between cell length and cell width compared to non-stimulated samples [323]. In addition, Kcnh2 and Kcnd2, which are voltage-gated potassium channels related to the human ether-ago-go gene (HERG), were upregulated in stimulated culture compared to the control.…”
Section: Electrical Stimulation Of Cardiac Constructsmentioning
confidence: 99%